Problematika Wali Murid Sekolah Muhammadiyah dalam Mendampingi Belajar Daring di Masa Pandemi Covid-19 - Istikomah, Istikomah; Churahman, Taufik; Romadlon, Dzulfikar Akbar (TADRIS: Jurnal Pendidikan Islam, 2020)
One of the effects of the Covid-19 pandemic is on the education sector with the implementation of the SFH policy which makes all teaching and learning activities carried out online. This study aims to determine the problems of guardians of elementary level Muhammadiyah school students in Sidoarjo Regency in accompanying online learning. This research uses a case study approach, the main research subject is the guardian of Muhammadiyah school students. The data collection method used is the Google Form questionnaire and interviews. The data analysis technique in this study consisted of three activity lines, data reduction, data presentation, and conclusion drawing. The results showed that there were 5 problems faced by the guardians of the students, namely: First, difficulties in mentoring. Second, the student's learning load is heavy. Third, internet quota and network problems. Fourth, the limitations of online learning media. Fifth, it is difficult to condition the children at Home.